Lessons to cancer from studies of leukemia and hematopoiesis - Brown, Geoffrey (Frontiers in Cell and Developmental Biology, 2022)
The starting point to describing the origin and nature of any cancer must be knowledge about how the normal counterpart tissue develops. New principles to the nature of hematopoietic stem cells have arisen in recent years. In particular, hematopoietic stem cells can ‘choose’ a cell lineage directly from a spectrum of the end-cell options, and are, therefore, a heterogeneous population of lineage affiliated/biased cells. These cells remain versatile because the developmental trajectories of hematopoietic stem and progenitor cells are broad. From studies of human acute myeloid leukemia, leukemia is also a hierarchy of maturing or partially maturing cells that are sustained by leukemia stem cells at the apex. This cellular hierarchy model has been extended to a wide variety of human solid tumors, by the identification of cancer stem cells, and is termed the cancer stem cell model. At least, two genomic insults are needed for cancer, as seen from studies of human childhood acute lymphoblastic leukemia. There are signature mutations for some leukemias and some relate to a transcription factor that guides the cell lineage of developing hematopoietic stem/progenitor cells. Similarly, some oncogenes restrict the fate of leukemia stem cells and their offspring to a single maturation pathway. In this case, a loss of intrinsic stem cell versatility seems to be a property of leukemia stem cells. To provide more effective cures for leukemia, there is the need to find ways to eliminate leukemia stem cells.